The Influence of Product Quality and Promotion on The Purchasing Decision Process for Consumers of Karyabera Perdana MSME Products - Munarsih; Ayu Dhita; Yhonanda Harsono; Muhammad Musyfiq (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This study aims to determine the effect of product quality and promotion Regarding Purchase Decision Process for Consumers of Karyabera Perdana UMKM Products Depok West Java. This research is associative with a quantitative approach. The sample of this study was determined using the slovin formula as many as 62 respondents. Data collection techniques by means of questionnaires, data analysis techniques with SPSS software version 25. Research results shows that: (1) Product quality influences decisions purchases with the regression equation Y = 6.796 + 0.821X1. Coefficient value correlation of 0.808. The coefficient of determination of 0.652 has an effect significant to purchasing decisions with the result t count > t table or (10.611 > 2.000) with a significance value t table or (10.2221 > 2.000) with a significance < 0.050 or (0.000 < 0.050). (3) Quality Products and Promotions affect purchasing decisions with a regression value of Y = 2.359 + 0.491X1 + 0.448X2. The correlation coefficient value is 0.862. The coefficient of determination is 0.742. Significant influence on purchase decision with the result Fcount > Ftable or (85.025 > 3.150). Significance value < 0.050 or (0.000<0.050) so in this study Ha can accepted.